Asymmetric Effects of Quality of Life on Residents’ Satisfaction: Exploring a Newborn Natural Disaster Tourism Destination - Derong Lin (MDPI AG, 2021)
Developing disaster tourism has become an important means of post-disaster recovery, but the relationship between attributes of quality of life (QOL) and residents’ satisfaction toward newborn natural disaster destination (NNDD) development has not been explored. This study examines the asymmetric effects of QOL on residents’ satisfaction using the dummy variable regression approach based on the Three-Factor Theory. A mixed-method approach was used to develop QOL scale, and a questionnaire was developed to survey 379 residents from China’s Wenchuan. This study identifies the types (positive asymmetric, symmetric, and insignificant effect) of seven QOL attributes that influence residents’ satisfaction. This study provides a valuable supplement to the literature on residents’ QOL by focusing on the NNDD context, and is a pioneering attempt to apply the Three-Factor Theory from the perspective of local residents. Practically, some implications for policy optimization are proposed to help NNDD development.